2015
DOI: 10.1093/jisesa/iev071
|View full text |Cite
|
Sign up to set email alerts
|

Contact Toxicity and Repellency of the Main Components From the Essential Oil ofClausena anisum-olensAgainst Two Stored Product Insects

Abstract: The essential oil of Clausena anisum-olens (Blanco) Merr. showed strong contact toxicity and repellency against Lasioderma serricorne and Liposcelis bostrychophila adults. The components of the essential oil obtained by hydrodistillation were determined by gas chromatography-mass spectrometry. It was found that the main components were myristicin (36.87%), terpinolene (13.26%), p-cymene-8-ol (12.38%), and 3-carene (3.88%). Myristicin and p-cymene-8-ol were separated by silica gel column chromatography, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Samples KN1 and KN2 contained the same food color azorubine [19], while sample KN3 contained amaranth [11]. …”
Section: Resultsmentioning
confidence: 99%
“…Samples KN1 and KN2 contained the same food color azorubine [19], while sample KN3 contained amaranth [11]. …”
Section: Resultsmentioning
confidence: 99%
“…In particular, MFO contained a discrete level of the volatile odor compound myristicin (49 mg/g; Piras et al, ). This compound has been reported to be the major factor for the contact toxicity of the Clausena anisum‐olens EO against Lasioderma serricorne and Liposcelis bostrychophila adults (You et al, ). Different components of M. fragrans EO showed insect toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that terpenoids and aromatic compounds exhibited excellent bioactivities against different stored product insect pests [29][30][31][32] and aldehydes showed fair contact toxicity and repellent activities [33]. Here, four representative compounds were selected from 26 components identified in our sample as they belong to the chemical types of monoterpenes, sesquiterpenes, aldehydes, or aromatic compounds, respectively.…”
Section: Chemical Constituents Of the Essentialmentioning
confidence: 99%